THE EFFECT OF INCENTIVES AND MOTIVATION ON EMPLOYEE SATISFACTION AT PT. CAPELLA MULTIDUND BRANCH PEKANBARU - Nurhayana Nurhayana (Sean Institute, 2022)
This study aims to determine the effect of incentives and motivation on employee job satisfaction at PT Capella Multidana Pekanbaru branch. The population in this study were employees of the PT Capella Multidana Pekanbaru branch. The sample in this research is 48 respondents. The sampling technique for respondents was carried out using simple random sampling technique. This research uses quantitative methods. Test the quality of the data using the classical assumption test. The analytical method used is multiple regression analysis, F test (simultaneous test), t test (partial test) and test the coefficient of determination. The results showed that the incentive variable had a positive and significant effect on the employee job satisfaction variable and the motivational variable had a positive and significant effect on the employee job satisfaction variable (through the F test). And from the results of the partial test (t test) it shows that the incentive variable has a positive and significant effect on the employee job satisfaction variable and the motivational variable has a positive and significant effect on the employee job satisfaction variable. Also, from the test results of the coefficient of determination, the adjusted R Square value shows a value of 0.428 or 42.8%), this shows that the ability of the independent variable is not strong enough to explain the dependent variable and the remaining 57.2% can be explained by other variables outside of this research variable